The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0171289
|View full text |Cite
|
Sign up to set email alerts
|

Seeing shapes in seemingly random spatial patterns: Fractal analysis of Rorschach inkblots

Abstract: Rorschach inkblots have had a striking impact on the worlds of art and science because of the remarkable variety of associations with recognizable and namable objects they induce. Originally adopted as a projective psychological tool to probe mental health, psychologists and artists have more recently interpreted the variety of induced images simply as a signature of the observers’ creativity. Here we analyze the relationship between the spatial scaling parameters of the inkblot patterns and the number of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
5
34
0
Order By: Relevance
“…The "man in the moon", induced by the lunar surface structure, is often referenced as a classical pareidolia existent since ancient times, although different cultures and observer positions see different faces or figures. Apart from its use in the context of Lewy body disease, it has been suggested that pareidolias do not, per se, reflect a pathologic sign, but instead a well-wired brain or even reflect creativity (26).…”
Section: What Is Pareidolia and Where Else Is It Useful?mentioning
confidence: 99%
See 4 more Smart Citations
“…The "man in the moon", induced by the lunar surface structure, is often referenced as a classical pareidolia existent since ancient times, although different cultures and observer positions see different faces or figures. Apart from its use in the context of Lewy body disease, it has been suggested that pareidolias do not, per se, reflect a pathologic sign, but instead a well-wired brain or even reflect creativity (26).…”
Section: What Is Pareidolia and Where Else Is It Useful?mentioning
confidence: 99%
“…Historically, the pareidolias evoked by looking at the random patterns of the Rorschach ink plots have been promoted as a "psychological X-ray" able to "unlock the hidden secrets of the human unconscious" (26). In more recent times, the ability to recognize shapes and figures in Rorschach plots has been viewed as more indicative of the observer's creativity (26).…”
Section: What Is Pareidolia and Where Else Is It Useful?mentioning
confidence: 99%
See 3 more Smart Citations